2012
DOI: 10.21608/jpp.2012.84992
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sweet Pepper Plants (Vegetative Growth and Leaf Chemical Constituents) to Organic, Biofertilizers and Some Foliar Application Treatments.

Abstract: This investigation was conducted in the two successive summer seasons of 2010 and 2011 on sweet pepper plants "Madir" hybride at a private farm at Sahragt El-Soghra near Mansoura, Dakahlia Governorate, Egypt to study the effect of two sources of organic fertilizers (chicken manure and compost), biofertilizers (a mixture of Azotobacter chroococcum and Bacillus circulans bacteria and Mycorrhiza fungi), some foliar application treatments (seaweed extract, yeast extract and humic acid) and their interaction on veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…The positive effects of seaweed treatment on the content of sugars and carbohydrates may be due to its enhancable effect on leaf area (photosynthetic surfaces), content of chlorophylls and content of some important minerals as shown by Dawa et al (2013) on pepper, similar findings was reported by Rathore et al (2009) on soybean and Hamed (2012) on snap bean. While the positive effect of yeast extract on quality parameters of pea is due to that yeast preparation contained carbohydrates, sugars, proteins, fatty acids, amino acids, hormones, macro and micro elements in suitable balance.…”
Section: Seed Qualitysupporting
confidence: 80%
See 1 more Smart Citation
“…The positive effects of seaweed treatment on the content of sugars and carbohydrates may be due to its enhancable effect on leaf area (photosynthetic surfaces), content of chlorophylls and content of some important minerals as shown by Dawa et al (2013) on pepper, similar findings was reported by Rathore et al (2009) on soybean and Hamed (2012) on snap bean. While the positive effect of yeast extract on quality parameters of pea is due to that yeast preparation contained carbohydrates, sugars, proteins, fatty acids, amino acids, hormones, macro and micro elements in suitable balance.…”
Section: Seed Qualitysupporting
confidence: 80%
“…The obtained increment of yield and its components may be due to increase of vegetative growth characters. Hence vigorous growth increase in turn the amount of metabolites synthesized and dry matter accumulation by the plants as mentioned by Dawa et al (2008) on pea and Dawa et al (2013) on pepper. Moreover, the increase in total green pod yield owe directly to increase in both number and weight of pods as well as green pod yield/plant.…”
Section: Yield and Its Componentsmentioning
confidence: 88%
“…Our finding connected with findings of Bhat et al (2010) who showed that the use of seaweed as an organic amendment increased the total chlorophyll content in tomato. Also Hamed (1997), El-Aidy et al (2002) and Dawa et al(2012) they indictaed that foliar application with seaweed extract increased N, P and K percentages in sweet pepper leaves.…”
Section: Effect Of Foliar Application On N P and K Percentagesmentioning
confidence: 97%
“…The same trend was obtained in the 2 nd season, similar results on tomato plants were obtained by Patil et al (2004), Bayoumi (2005), Jagadeesha (2008), Mahila et al (2010). Also, Dawa et al (2012) on pepper plant found that foliar application of seaweed extract with chicken manure as a source of organic fertilization in presence of bio fertilizers enhanced vegetative plant growth, N, P and K percentages in leaves. Khan et al (2012) reported that biofertilizers (Azotobacter+ Azospirillum) combined with organic fertilizer+ 100% recommended N gave the highest values of plant height and number of leaves of pepper plants than using organic or bio-fertilizers alone.…”
Section: Effect Of Triple Interactionmentioning
confidence: 99%
See 1 more Smart Citation